Evaluation of functional outcome of distal tibial fractures stabilized with distal tibial locking plate - Kumar, Naveen; Thakur, Manoj; Kashyap, Sandeep (International Journal of Research in Orthopaedics, 2020)
Background: The present study is an attempt to evaluate the results of locking compression plate for distal tibia in lower tibial fractures using open reduction internal fixation and minimally invasive plate osteosynthesis technique. Methods: Prospective and retrospective study was conduct on patients attending the outpatient department (OPD)/Emergency OPD in Indira Gandhi Medical College, Shimla during September 2015 to August 2016 with distal tibial fractures. The patients treated with locking compression plates using minimally invasive plate osteosynthesis (MIPO) or open reduction internal fixation (ORIF) are reviewed for inclusion and exclusion criteria. All data were collected and analyzed by Epi-info software. Results: Out of 52 patients, 48.4% patients undergo open reduction internal fixation had excellent results and 28.6% patients undergo surgery by MIPPO technique had excellent results. p value is 0.352 which is not significant. Overall, 40.4% patients had excellent results. In our study, 32.6% patients having AO/OTA type A fractures had excellent score while type B and C had 1.9% excellent score. This is attributed to more comminution and involvement of ankle joint. Overall, 40.4% patients had excellent score. P value is 0.863 which is insignificant. Conclusions: We observed excellent/ good functional outcome in 65.3% of patients.